2013
DOI: 10.1111/acel.12182
|View full text |Cite
|
Sign up to set email alerts
|

The aging signature: a hallmark of induced pluripotent stem cells?

Abstract: The discovery that somatic cells can be induced into a pluripotent state by the expression of reprogramming factors has enormous potential for therapeutics and human disease modeling. With regard to aging and rejuvenation, the reprogramming process resets an aged, somatic cell to a more youthful state, elongating telomeres, rearranging the mitochondrial network, reducing oxidative stress, restoring pluripotency, and making numerous other alterations. The extent to which induced pluripotent stem cell (iPSC)s mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 60 publications
(89 reference statements)
5
64
0
1
Order By: Relevance
“…3A) as reported in earlier findings (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). We reprogrammed SkMs from both young and old mice using classic Yamanaka factors, and colonies were stained with alkaline phosphatase (ALP) on day 16–18 and counted to assess reprogramming efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A) as reported in earlier findings (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). We reprogrammed SkMs from both young and old mice using classic Yamanaka factors, and colonies were stained with alkaline phosphatase (ALP) on day 16–18 and counted to assess reprogramming efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that older and senescent cells are more resistant to reprogramming (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). These observations have established the importance of current efforts underway to understand the biology of cell reprogramming in the context of chronological and replicative age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to representing great therapeutic potential, iPSC-derived cells have proven to be very useful tools for understanding disease pathogenesis. 27,35 For these studies, we used an iPSC line (006-BIOTR-0001) obtained from the Mayo Clinic Center for Regenerative Medicine BioTrust. The successful generation of iPSCs from somatic skin fibroblasts was confirmed by the presence of the pluripotency markers Oct4, SSeA4, Nanog, Tra1-60, and Sox1 ( Supplementary Figs.…”
Section: Characterization Of Ipsc-rpementioning
confidence: 99%
“…100,101 As a result, resident cardiac stem/progenitor cells in older humans are expected to have a decreased reparative capacity in response to myocardial injury. Consequently, there is considerable interest in rejuvenating the endogenous CPCs.…”
Section: Rejuvenation Of Cardiac Stem Cellsmentioning
confidence: 99%